Effect of Stirring Co-digestion of Palm Oil and Fruith for Biogas Production to Increase Economy Benefit - Cut Susan Octiva; Indriyani Indriyani; Ari Beni Santoso (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Effect of stirring on palm oil mill (POME) and empty fruith bunch (EFB) substrate mixture in increasing the biogas production is done at batch reactor with 8 liters of working 6 liters with thermophilic temperature. Co-digestion POME and EFB were performed by varying the stirring rate (50, 100, 150, 200 and 300 rpm). The best stirring rate was obtained at 100 rpm stirring which reached 84.82 L/mg.VS and biogas production reached 88.53%, and VS reduction of 20.30%.